2012
DOI: 10.4067/s0717-95022012000300051
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Retromolar Foramen in Human Mandibles: Ethnic and Clinical Aspects

Abstract: SUMMARY:The retromolar foramen allows the passage of the neurovascular bundles that contribute to nutrition and innervation of the pulp and periodontium of the lower teeth. Knowledge of this anatomical variation may prevent complications in the anesthesia and surgical procedures in this area and serve as an anatomical landmark for ethnic identification. The aim of this study was to evaluate the impact of the retromolar foramen in human mandibles of adult Brazilians and discuss the clinical and ethnic related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 9 publications
1
29
2
Order By: Relevance
“…Notwithstanding that, other studies have demonstrated RMCs more frequently on the left side than on the right side 5,25 . In the present study, the presence of RMC occurred more frequently in females, though the literature have not identified and gender predilection 21,22 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Notwithstanding that, other studies have demonstrated RMCs more frequently on the left side than on the right side 5,25 . In the present study, the presence of RMC occurred more frequently in females, though the literature have not identified and gender predilection 21,22 .…”
Section: Discussionmentioning
confidence: 97%
“…The presence of RMC has been reported by some authors in different populations, showing its increasing incidence [2][3][4][5] . There have only been a few published studies on this subject and there is no current systematic review on the prevalence of RMC and its clinical implications, namely risk of inferior alveolar nerve block failures, accidents and surgical complications such as paresthesia and hemorrhage 9,10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 In addition, the presence of the dental canal has clinical implications for extraction and endodontic treatment because of the potential for lateral canals in the root canal. 3,39 Anaesthesia failure in the inferior alveolar nerve may be associated with the presence of BMCs, especially when there are two mandibular foramens. Particularly, the suspicion of an anatomic variation should be taken into account when anaesthesia appears to have reached the ipsilateral lip and chin but not the teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Foramina occur in 10% of retromolar fossa and infiltration in this region can abolish sensation which occasionally remains after an inferior alveolar nerve block. 3 Ossenberg 4 analysed 2500 mandibles for the retromolar foramina and stated that these foramina are more common in native populations of North America than in other part of the world namely India, Europe, Africa, & Northeast Asia. They occur more commonly unilaterally than bilaterally.…”
Section: Introductionmentioning
confidence: 99%